1997
DOI: 10.1152/ajpendo.1997.272.6.e976
|View full text |Cite
|
Sign up to set email alerts
|

Age-related increase in muscle sympathetic nerve activity is associated with abdominal adiposity

Abstract: Tonic sympathetic nerve activity (SNA) increases with age, but the mechanisms are unknown. There is evidence that SNA is positively related to total and abdominal body fat, which also increase with age. We tested the hypotheses that 1) the elevation in SNA with age is partially accounted for by higher abdominal and/or total body fat and 2) skeletal muscle is a target of the adiposity-related sympathetic effects. Direct microneurographic recordings of skeletal muscle SNA (MSNA) were obtained during supine rest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 19 publications
4
51
1
Order By: Relevance
“…We 16,17 have previously reported that waist circumference (ie, abdominal adiposity) is an important determinant of the age-related increase in basal MSNA in humans. Taken together with the results of the present study, these finding suggest that elevated abdominal visceral fat is an important determinant of basal MSNA in male humans.…”
Section: Discussionmentioning
confidence: 97%
“…We 16,17 have previously reported that waist circumference (ie, abdominal adiposity) is an important determinant of the age-related increase in basal MSNA in humans. Taken together with the results of the present study, these finding suggest that elevated abdominal visceral fat is an important determinant of basal MSNA in male humans.…”
Section: Discussionmentioning
confidence: 97%
“…Jones and colleagues (Jones et al, 1996) reported that the gender difference in MSNA was no longer present after adjusting for differences in the waist-to-thigh ratio. Similarly, age-related differences in MSNA are reduced after adjusting for differences in waist circumference between young and older men (Jones et al, 1997a, Jones et al, 1997b. Whether the greater abdominal visceral fat accumulation that is characteristic of the metabolic syndrome, type 2 diabetes and hypertension also contributes to the higher MSNA levels observed in these disorders is not known.…”
Section: Sympathetic Neural Activation In Obesity: Role Of Abdominalmentioning
confidence: 99%
“…33,34 Accordingly, metabolic syndrome is considered to be a comprehensive perspective based on interactions between cardiovascular risk factors such as obesity, diabetes, dyslipidemia and chronic inflammation, 27 and related with sympathetic hyperactivity or tachycardia.…”
Section: Mechanismsmentioning
confidence: 99%